Effect of sowing date and seed rate on yield performance of two mustard varieties - Afroz, MM; Sarkar, MAR; Bhuiya, MSU; Roy, AK (Journal of the Bangladesh Agricultural University, 2011)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from November 2007 to March 2008 to study the effect of sowing date and seed rate on the yield and yield components of two mustard varieties. The treatments included two varieties viz. BARI Sarisha-9 and BARI Sarisha-6; three sowing date viz. 10, 20 and 30 November, and three seed rates viz. 8, 10 and 12 kg seeds ha-1. The experiment was laid out in a split plot design with three replications. It was observed that the variety had significant influence on the yield and yield contributing characters except non-effective pods plant-1, non-effective seeds pod-1 and 1000-seed weight. Higher seed yield was obtained by the variety BARI Sarisha-9. The highest seed yield (1.53 t ha-1) was recorded in 10 November sowing and the lowest one was achieved in 30 November sowing. Seed rate had also significant effect on plant height, branches plant-1, pods plant-1, effective pods plant-1, pod length, no. of seeds pod-1 and seed yield. The seed rate 8 kg ha-1 produced the highest seed yield (1.49 t ha-1) and the lowest seed yield was produced by 12 kg seeds ha-1. Among the yield contributing characters only harvest index and non-effective pods plant-1 were significantly influenced by the interaction of variety and date of seeding as well as the interaction of variety and seed rate. The highest seed yield (1.63 t ha-1) was produced when BARI Sarisha-9 was sown on 10 November. In case of interaction between variety and seed rate, BARI Sarisha-9 with 10 kg seeds ha-1 produced the maximum seed yield. Results further showed that the interaction of 10 November sowing with 8 kg seeds ha-1 produced the highest seed yield (1.55 t ha-1). Keywords: Mustard; Variety; Date of Seeding; Seed Rate; Seed Yield DOI: http://dx.doi.org/10.3329/jbau.v9i1.8737 JBAU 2011; 9(1): 5-8